Focal (segmental) dyshidrosis in syringomyelia. Issue 1 (1st July 1999) - Sudo, Kazumasa; Fujiki, Naoto; Tsuji, Sachiko; Ajiki, Minoru; Higashi, Takuya; Niino, Masaaki; Kikuchi, Seiji; Moriwaka, Fumio; Tashiro, Kunio
Abstract : The features or mechanisms of dyshidrosis have not been sufficiently clarified. Neither has the difference between hyperhidrosis and hypohidrosis. To clarify the features and mechanisms of dyshidrosis (hyperhidrosis and hypohidrosis) in syringomyelia, the clinical features focusing on hidrosis of 30 patients with syringomyelia and Chiari malformation located from a syringomyelia database were prospectively analysed. The patients were classified into three groups: eight patients (26.7%) had segmental hypohidrosis, 10 (33.3%) had segmental hyperhidrosis, and 12 (40.0%) had normohidrosis. We found that the Karnofsky functional status for the hyperhydrosis and normohidrosis groups were significantly higher than for the hypohidrosis group (p=0.0012), with no significant differences between the hyperhidrosis and normohidrosis groups. The duration from the onset of syringomyelia to the current dyshidrosis was significantly longer in the hypohidrosis group than in the hyperhidrosis group (p=0.0027). A significant correlation was identified between the duration from the onset of syringomyelia to the time at study and the performance score ( r =−0.599, p=0.0003). The results substantiate previous hypotheses that in its early stage syringomyelia causes segmental hyperactivity of the sympathetic preganglionic neurons, and hyperactivity of these gradually subsides as tissue damage progresses. Focal hyperhidrosis may be regarded as a hallmark of a relatively intact spinal cord, as well as normohidrosis.